Overview of The Value of C-Reactive Protein Against The Incidence of Sars-Cov-2 Disease - Maghfira Darma Burhani (Journal Research of Social Science, Economics, and Management, 2022)
Coronavirus disease 2019 (COVID-19) is a disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 or SARS-CoV-2. Symptoms caused by the corona virus include mild to severe and serious respiratory tract infections. C-Reactive Protein is one of the acute phase proteins synthesized in the liver to monitor disease both non-specifically and systemically. C-Reactive protein examination can detect acute phase inflammation which can be used to predict the presence of inflammation in patients. The purpose of this study was to determine the results of the examination of C-Reactive Protein Levels of patients suspecting SARS-CoV-19.This research is a descriptive research with purposive sampling technique. The sample size in this study was 30 samples. This research was conducted at the Humana Peima Hospital from March to May 2022. The research data were analyzed descriptively. Based on the results of the research that has been carried out, it can be seen that the patients suspected of SARS-CoV-19 with positive CRP results were 24 patients with a percentage of 80% and negative CRP results as many as 6 patients with a percentage of 20%.